Numerical investigation on non-Newtonian melting heat transfer of phase change material composited with nanoparticles and metal foam in an inner heated cubic cavity. (July 2022) - Zhuang, Yijie; Lin, Junjiang; Liu, Aihua
Abstract: In this paper, the non-Newtonian melting heat transfer of a latent heat thermal energy storage (LHTES) system composited with phase change material (PCM), nanoparticles and metal foam is numerically investigated inside an internal heated cubic cavity. The enthalpy-porosity method and power-law fluid model are adopted to model melting process for nano-enhanced PCM, and the Darcy-Forchheimer law and local thermal non-equilibrium model are assumed for metal foam. The effects of Rayleigh number ( Ra ), nanoparticle fraction ( Φ ), metal foam porosity ( ε ) and heater size on evolvement of solid-liquid interface, temperature of liquid PCM ( θ nf ) and metal foam ( θ s ), and full melting are addressed. The results reveal that with the increase of Ra, the convective heat transfer of PCM dominates the melting characteristic of the composite LHTES unit and accelerates the melting rate. With the increase in Φ, the non-Newtonian rheological behavior of liquid PCM is more pronounced with erratic convection flow due to increase of consistency parameter. Moreover, the convective heat transfer enhancement of θ nf with addition of nanoparticles compensates for the conductive heat transfer enhancement of θ s with increased ε . The internal heater size also plays an important role in the melting performance of composited PCM. Highlights: Non-Newtonian melting performance of NEPCM is numerically investigated. Increasing Ra enhances convective heat transfer. Analysis of coupling effects of Φ and ε on LTNE. Increase of internal heater size enhances LHTES performance.